Development of E-Book Learning Media Based on Problem Solving in the Material of the Human Digestive System - Mahrawi, Mahrawi; Istikomah, Umu; Ratnasari, Dwi (Science Education and Application Journal, 2021)
Abstract : This research aims to develop e-book learning media using the professional Flip pdf application based on problem solving in human digestive system materials and to test the feasibility of e-book media developed through validation of Experts and to find out the effectiveness of teacher and student responses. Is a type of research development / Research and development that uses 4D models with stages (define, design, develop and desiminate) in this study only up to the stage of develope.descriptive qualitative research design. E-book as a free variable and human digestive system as a bound variable. The population in the study was 18 students of class XI AL-khairiyah High School 4 Cilegon, school year 2021/2022. Data retrieval and collection techniques are carried out by spreading questionnaires and interviews, data analysis techniques using interpretase scales and likert scales to test the feasibility of e-books that have been created. The results of the assessment of media experts, obtained a score of 82% and and expert test material obtained a value of 79% which falls into the category of feasible while the response test of the student response test obtained a score of 88% and the teacher board 81% with a very interesting category, based on the results of the study can be concluded that: e-book human suppression system based on problem solving is suitable for student use in biological learning system materials. Keywords:biological learning, e-book, human digestive system, problem solvingÂ